Avaliação da produção de biopolímeros pelas cepas bacterianas DsA.N042 e DsA.N049 isoladas de Diabrotica speciosa usando subprodutos industriais - Denadae, Bárbara Evelin (2018)
The global development has enabling the improvement of daily life to human. However, the large production of manufactured materials such as plastics, it has generating environmental unbalanced, especially when they are discarded in an inappropriate manner. Due to this environmental concern, several researches have been carried out looking for materials as same mechanical properties of petroleum-based plastics, however, plastic-environmental friendly. In this context, bioplastics are a good alternative to replacing the petroleum-based plastics since they can be obtained in production processes that are less aggressive to the environment, and easily degraded. Microorganisms such as bacteria are a important source of the bioplastics. They can synthesize them naturally when subjected to specific growth conditions. Another advantage to the use of bacteria in the biotechnological production of (bio) molecules is the use of alternative substrates such as industrial waste (subproducts). Thus, the present study aimed to identify two strains of bacteria from Diabrotica speciosa's gut using 16S rDNA sequencing methodologies, and through fatty acid profiling by gas chromatography-mass spectrometry, as well as to assess their technical and economic viability in the production of biopolymers using industrial subproducts. It was not possible to identify the strains at species level, suggesting new species not described in the literature yet. However, the genera found for the strains in this study were identified as Aureimonas sp. and Delftia sp. The results for the fatty acid profiling showed a wider variety of molecules for Delftia sp. (15 different types) than to Aureimonas sp. (10 types of molecules), although both of they contained palmitic and stearic acid as major compounds. The investigated microorganisms were able of to use glycerol and whey as sources of nutrients to produce biopolymers (polyhydroxyalkanoates), in different concentrations. For Aureimonas sp., the concentration of glycerol and whey that presented the highest yield of biopolymer recovery were 2.0 and 10.0% (v/v), respectively. In its turn, the results for Delftia sp. indicated that 6.0 and 5.0% (v/v) of glycerol and whey, respectively, were the best concentrations evaluated to production of biopolymers in all treatments. The batch using whey at 5.0% (v/v) and the strain of Delftia sp., it produced 38.7% of PHB/cell dry weight, proving the feasibility of the use of the subproducts such as whey to produce biopolymers, as well as the importance to look for microorganisms in new microbiomes.